1982
DOI: 10.1149/1.2123955
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cathodic Polarization on the Creep Rate of Gold

Abstract: Annealed gold wires were loaded at 0 mV vs. SCE. The specimens were then polarized during 1 rain intervals to successively more negative potentials ranging from -200 to -1800 mV in steps of 200 inV. The extra strains measured as a function of the electrode potential had a characteristic distribution depending on the composition, oxygen content, and pH of the test solution. In general there are two peaks. In deaerated alkaline solutions a first peak occurred between -200 and -600 mV. This peak was completely ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The impact of γ on plasticity is further emphasized by studies of engineering materials wetted by electrolytes. These reveal similarities between the electrode-potential dependence of γ and creep rate 19 , 20 or fracture stress 21 . Zero-creep experiments typically use wires a few tens of μm in diameter and very low stresses, in the order of 10–100 kPa.…”
Section: Introductionmentioning
confidence: 65%
“…The impact of γ on plasticity is further emphasized by studies of engineering materials wetted by electrolytes. These reveal similarities between the electrode-potential dependence of γ and creep rate 19 , 20 or fracture stress 21 . Zero-creep experiments typically use wires a few tens of μm in diameter and very low stresses, in the order of 10–100 kPa.…”
Section: Introductionmentioning
confidence: 65%
“…The phenomenon is confirmed by studies of engineering materials wetted by electrolytes. These reveal similarities between the electrode-potential dependence of γ and creep rate or fracture stress . The recent approach using in situ experiments with nanoporous gold suggests opportunities for exploring the analogous behavior for plastic flow and for structures with much smaller characteristic size.…”
Section: Surface-induced Tension−compression Asymmetry?mentioning
confidence: 81%
“…From creep tests on thin gold wires in various electrolyte solutions, it has been concluded that dislocations emerging at the surface of a loaded specimen can be pinned by certain chemisorbed ions or by adsorbed oxygen containing species, including OH -ions and water molecules (1)(2)(3).…”
mentioning
confidence: 99%
“…(In chloride or other complexing solutions, different mechanisms may occur.) (NiOH)ad, is expected to form as a result of the strong interactions between nickel and water Ni + H~O ~ (NiOH)~d~ + H § + e [1] It may be removed from the nickel surface by cathodic polarization (NiOH)ads + H + + e ---> Ni + H20 [2] or (NiOH)ads + e ~ Ni + OH [3] At constant potential (NiOH)ad, may be removed by lowering the pH, again following reaction [2]. Our data may be compared with the findings of Bockris, Reddy, and Rao (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation